The Posthuman Pedagogy: A Learning Centric Educational Dimension - Dhungana, Siddhartha (Bodhi: An Interdisciplinary Journal, 2023)
The article is based on a thematic analysis of available literature on posthuman educational practices and opportunities. It asserts that the posthuman context does not demoralize human space, but rather strengthens educational practices by going beyond formal and informal education and surpassing teacher-centered or student-centered teaching-learning activities. The article discusses perceptions of the posthuman context in general, as well as common educational practices about the posthuman context. Its primary focus is on posthuman pedagogical considerations and a method to incorporate digital realities as a strength to posthuman pedagogue. It proposes a multisensory pedagogy that incorporates human and nonhuman realities to promote lifelong learning procedures. It also asserts the concept of a diffractive teacher who transforms into a barycentric mass collaborating and functioning in a relational approach.